Influence of dissolved hydrogen on the viscosity and interfacial tension of the liquid organic hydrogen carrier system based on diphenylmethane by surface light scattering and molecular dynamics simulations. (29th November 2022) - Kerscher, Manuel; Klein, Tobias; Preuster, Patrick; Wasserscheid, Peter; Koller, Thomas M.; Rausch, Michael H.; Fröba, Andreas P.
Abstract: In hydrogenation and dehydrogenation processes of liquid organic hydrogen carriers (LOHCs), molecular hydrogen (H2 ) is present, but its influence on the thermophysical properties of the LOHC compounds is still hardly known. This study provides experimental results from surface light scattering and predictions from molecular dynamics simulations on the influence of dissolved H2 on the liquid viscosity, interfacial tension, and liquid density of the LOHC system based on diphenylmethane at varying degree of hydrogenation, process-relevant temperatures up to 573 K, and pressures up to 7 MPa. First-time measurements of the viscosity of bicyclic hydrocarbon compounds in the presence of dissolved H2 at saturation conditions reveal a negligible effect of pressure. The interfacial tension decreases independently of the LOHC composition by about 6% at 7 MPa. The simulations can adequately represent the effect of H2 on the interfacial tension and evidence a weak enrichment of H2 at the interface. Graphical abstract: Image 1 Highlights: Experimental and simulation data on thermophysical properties up to 523 K and 7 MPa. Negligible effect of dissolved hydrogen on viscosity of diphenylmethane-based LOHCs. Decreasing interfacial tension with increasing hydrogen pressure by up to 6%. Surface enrichment of hydrogen molecules in LOHCs evidenced by simulations. Simulations can describe the influence of H2 on the interfacial tension and density.